PENGGUNAAN POLISEMI PADA KOLOM WACANA SURAT KABAR PONTIANAK POST EDISI JANUARI 2018 - Erwansah, Erwansah; Sulissusiawan, Ahadi; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractPolysemy is a language phenomena that show a word has more than one meaning. This polysemy divide according to their form, meaning, and function. There is a lot of polysemy on discourse column. This column has a serial of sentence which correlated each other. Pontianak Post newspaper is the data resource on this research. The issue is about form, meaning, and function of polysemy. This research conducted by documentary approach.According to the research, we can conclude a few things. First, there are fivety forms of polysemy. The polysemy form analyzed through their linguistic form. Second, each polysemy has their own meaning. But, it changes according to their context. Third, polysemy function is correlated with syntaxs function.Polysemy may transform in to subject, predicate, or object. Â Keywords: Polysemy, Discourse, Pontianak Post